2023
DOI: 10.1002/smll.202300147
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Functional Carbon Nitride by Implanting Semi‐Isolated VO2 Active Sites for Photocatalytic H2 Production and Organic Pollutant Degradation

Abstract: It is critical to facilitate surface interaction for liquid–solid two‐phase photocatalytic reactions. This study demonstrates more advanced, efficient, and rich molecular‐level active sites to extend the performance of carbon nitride (CN). To achieve this, semi‐isolated vanadium dioxide is obtained by controlling the growth of non‐crystalline VO2 anchored into sixfold cavities of the CN lattice. As a proof‐of‐concept, the experimental and computational results solidly corroborate that this atomic‐level design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…4f, for N 1s, the three peaks located at 398.6, 399.8 and 401.2 eV are ascribed to sp2-hybridized nitrogen (CN–C), sp 3 -hybridized nitrogen (N–(C) 3 ) and amino functional group coupled carbon (C–N–H), respectively. 41 The XPS spectra further demonstrated that the NiCo 2 O 4 nanoparticles were successfully anchored onto the g-C 3 N 4 nanosheets.…”
Section: Resultsmentioning
confidence: 87%
“…4f, for N 1s, the three peaks located at 398.6, 399.8 and 401.2 eV are ascribed to sp2-hybridized nitrogen (CN–C), sp 3 -hybridized nitrogen (N–(C) 3 ) and amino functional group coupled carbon (C–N–H), respectively. 41 The XPS spectra further demonstrated that the NiCo 2 O 4 nanoparticles were successfully anchored onto the g-C 3 N 4 nanosheets.…”
Section: Resultsmentioning
confidence: 87%